(untitled) (Bangladesh Heart Journal, 2018)
Introduction: The burden of CAD is increasing at a greater rate in South Asia than in any other region globally. Among them acute ST elevation myocardial infarction (STEMI) is one of the leading causes of death and disability. Major aspect of treatment of acute STEMI is reperfusion of the infarct related artery. Delay in reperfusion is associated with higher mortality and morbidity rates. While primary percutaneous coronary intervention (PCI) is the preferred mode of reperfusion, only few patients can get this form of reperfusion within recommended timelines. On the other hand, thrombolysis is easily available, economical and evaluated in several clinical studies. Thrombolysis is an important reperfusion strategy, especially when primary PCI cannot be offered to STEMI patients, with a time dependent fashion. Methods: This randomized controlled trial was conducted in the department of Cardiology of National Institute of Cardiovascular Diseases since January 2016 to June 2018. Objective of the study was to find out the outcomes of acute STEMI patients after getting on-shelve or purchased Streptokinase (STK). Initially there was no free supply of STK in our hospital as it is an expensive drug, later on fund was arranged and STK was made available at free of cost by the hospital authority. Total 300 patients fulfilling inclusion and exclusion criteria were included in the study. Group I: 150 patients received on-shelf STK when it was made free by the authority and Group II: 150 patients received purchased STK when it was not available at free of cost. Study populations were analyzed for LVF, Cardiogenic shock, MACE (re-infarction, stroke and death) and duration of hospital stay. Results: The mean age of the study population in group I and II were 53.88 ± 14.51 vs. 57.18 ± 15.28 years (p= 0.46). Mean door to injection time in group I and II were 25.51 ± 7.9 vs. 70.36 ± 16.6 minutes (p=<0.001). ST segment resolution was significantly higher in on-shelf STK group then purchased group which were 109 (72.7%) vs. 92 (61.3%), p=0.03. Considering the in-hospital outcome we found that in group I and group II LVF (killip III/IV) was 10 (6.7%) vs. 23 (15.3%) , Cardiogenic shock was 11 (7.3%) vs. 24(16%) , re-infarction was 9(6%) vs. 13 (8.7%) , Stroke was 6 (4%) vs. 8 (5.3%) and death was 12 (8%) vs. 23(15.3%). Among them LVF (killip III/IV), Cardiogenic shock and Death were significantly higher in group II (p=0.02, 0.01 and 0.04 respectively). Major adverse cardiac events (MACE) included re-infarction, Stroke and death, were significantly higher in group II [27 (18%) vs. 44(29.3), p= 0.02]. Mean hospital stay was significantly higher in group II (6.05 ± 1.81) then group I (5.33±1.26), (p=<0.001). Multivariate logistic regression analysis showed hypertension (p=.025) and door to injection time (p=.002) were statistically significant predictors for in-hospital major advance cardiac events (re-infarction, stroke and death) after streptokinase therapy. Conclusion: Despite the strength of evidence based medicine pertaining to the benefits of primary PCI in STEMI, treatment options in Bangladesh are often dictated by resources, logistics, availability and affordability. In our country, not many hospitals offer primary PCI services round the clock. So thrombolysis by streptokinase it the potential reperfusion strategy in our context. In our study it has been found that onshelf Streptokinase significantly reduce door to injection time which ultimately reduce cardiovascular mortality and mortality and also significantly reduce hospital stay. Hospitals intended to treat acute STEMI patients should have on-shelve Streptokinase to reduce door to injection time which affect the inhospital outcome by reducing significant cardiovascular mortality and morbidity. Bangladesh Heart Journal 2018; 33(2) : 126-133